Diagnostic and Therapeutic Uptake of Intrathyroid Metastasis of Midgut Neuroendocrine Tumor on 68Ga-DOTANOC PET/CT and 177Lu-DOTATATE Imaging. (July 2019) - Vija Racaru, Lavinia; Sinigaglia, Mathieu; Fontaine, Sebastien; D'Aure, Dominique; Courbon, Frederic; Dierickx, Lawrence
Abstract : Abstract: A 58-year-old woman with 5-year history of grade 1 progressive metastatic intestinal neuroendocrine tumor with metachronous liver metastases initially treated by surgery and liver embolization underwent 68 Ga-DOTANOC PET/CT before 177 Lu-DOTATATE therapy. 68 Ga-DOTANOC PET/CT revealed increased uptake in several liver metastases and right iliac lymph nodes, consistent with radiopeptide therapy, including a hypodense isthmic thyroid nodule. Fine needle ultrasound-guided biopsy of the thyroid nodule was realized. Immunohistochemistry was positive for CD56, chromogranin, and synaptophysin and negative for calcitonin, confirming neuroendocrine tumor intrathyroid metastasis. 177 Lu-DOTATATE SPECT/CT showed therapeutic uptake on the thyroid metastasis.